The Two Faces of Nematode Infection: Virulence and Immunomodulatory Molecules From Nematode Parasites of Mammals, Insects and Plants - Bobardt, Sarah D.; Dillman, Adler R.; Nair, Meera G. (Frontiers in Microbiology, 2020)
Helminths stage a powerful infection that allows the parasite to damage host tissue through migration and feeding while simultaneously evading the host immune system. This feat is accomplished in part through the release of a diverse set of molecules that contribute to pathogenicity and immune suppression. Many of these molecules have been characterized in terms of their ability to influence the infectious capabilities of helminths across the tree of life. These include nematodes that infect insects, known as entomopathogenic nematodes (EPN) and plants with applications in agriculture and medicine. In this review we will first discuss the nematode virulence factors, which aid parasite colonization or tissue invasion, and cause many of the negative symptoms associated with infection. These include enzymes involved in detoxification, factors essential for parasite development and growth, and highly immunogenic ES proteins. We also explore how these parasites use several classes of molecules (proteins, carbohydrates, and nucleic acids) to evade the host’s immune defenses. For example, helminths release immunomodulatory molecules in extracellular vesicles that may be protective in allergy and inflammatory disease. Collectively, these nematode-derived molecules allow parasites to persist for months or even years in a host, avoiding being killed or expelled by the immune system. Here, we evaluate these molecules, for their individual and combined potential as vaccine candidates, targets for anthelminthic drugs, and therapeutics for allergy and inflammatory disease. Last, we evaluate shared virulence and immunomodulatory mechanisms between mammalian and non-mammalian plant parasitic nematodes and EPNs, and discuss the utility of EPNs as a cost-effective model for studying nematode-derived molecules. Better knowledge of the virulence and immunomodulatory molecules from both entomopathogenic nematodes and soil-based helminths will allow for their use as beneficial agents in fighting disease and pests, divorced from their pathogenic consequences.